The link between amyloid β and ferroptosis pathway in Alzheimer’s disease progression - Naďa Majerníková; Alejandro Marmolejo-Garza; Casandra Salinas Salinas; Minh D. A. Luu; Yuequ Zhang; Marina Trombetta-Lima; Tamara Tomin; Ruth Birner-Gruenberger; Šárka Lehtonen; Jari Koistinaho; Justina C. Wolters; Scott Ayton; et al. (Cell Death and Disease)
Abstract Alzheimer’s disease (AD) affects millions of people worldwide and represents the most prevalent form of dementia. Treatment strategies aiming to interfere with the formation of amyloid β (Aβ) plaques and neurofibrillary tangles (NFTs), the two major AD hallmarks, have shown modest or no effect. Recent evidence suggests that ferroptosis, a type of programmed cell death caused by iron accumulation and lipid peroxidation, contributes to AD pathogenesis. The existing link between ferroptosis and AD has been largely based on cell culture and animal studies, while evidence from human brain tissue is limited. Here we evaluate if Aβ is associated with ferroptosis pathways in post-mortem human brain tissue and whether ferroptosis inhibition could attenuate Aβ-related effects in human brain organoids. Performing positive pixel density scoring on immunohistochemically stained post-mortem Brodmann Area 17 sections revealed that the progression of AD pathology was accompanied by decreased expression of nuclear receptor co-activator 4 and glutathione peroxidase 4 in the grey matter. Differentiating between white and grey matter, allowed for a more precise understanding of the disease’s impact on different brain regions. In addition, ferroptosis inhibition prevented Aβ pathology, decreased lipid peroxidation and restored iron storage in human AD iPSCs-derived brain cortical organoids at day 50 of differentiation. Differential gene expression analysis of RNAseq of AD organoids compared to isogenic controls indicated activation of the ferroptotic pathway. This was also supported by results from untargeted proteomic analysis revealing significant changes between AD and isogenic brain organoids. Determining the causality between the development of Aβ plaques and the deregulation of molecular pathways involved in ferroptosis is crucial for developing potential therapeutic interventions.